Genetic dynamics of flowering date evolved from later to earlier in annual wild and cultivated soybean in China. Issue 4 (17th May 2021) - Liu, Fangdong; He, Jianbo; Wang, Wubin; Xing, Guangnan; Zhao, Jinming; Li, Yan; Gai, Junyi
Abstract: At its center of origin, the Chinese soybean germplasm pool (CSGP) consists of annual wild (WA), farmers' landrace (LR), and released cultivar (RC) populations. A representative sample (1, 024 accessions) was studied for genetic dynamics of days to flowering (DTF) shortening in two evolutionary processes (WA→LR→RC and southern→northern) via direct comparisons of quantitative trait loci (QTL)–allele matrices among populations and subpopulations using a restricted two‐stage multilocus genome‐wide association analysis (RTM‐GWAS). In CSGP, 177 DTF QTL with 797 alleles explaining 95.1% phenotypic variation were identified and organized into a DTF QTL–allele matrix and its component submatrices. (i) Allele inheritance, emergence, exclusion. and recombination were major genetic drivers of DTF‐shortening for WA→LR→RC. (ii) Genetic drivers for southern→northern differed between wild and cultivated soybean [ Glycine max (L.) Merr.], with less allele exclusion, more allele emergence, and slighter allele change in WA than in LR plus RC. (iii) The LR furthest south (LRIV ) was recognized as the primitive LR subpopulation, as it had the most wild alleles and newly formed QTL and alleles. (iv) Combining the WA→LR→RC and southern→northern processes, the DTF shortening was divided into four periods: WASouth →WANorth, WASouth →LRSouth, LRSouth →LRNorth, and LR→RC; the per‐year allele change rate in LR→RC exceeded the others (backward in turn), and breeding effort accelerated allele emergence and exclusion (changed). (v) Out of 177 loci and 797 alleles, 83 and 207, respectively, changed in WA→LR→RC and southern→northern processes, especially eight new loci emerged in LR and RC; in total, 81 candidate genes were annotated and grouped into six flowering‐related biological processes. (vi) Further DTF shortening (4.2–11.1 d) in CSGP was predicted. This study comprehensively explored the evolutionary mechanism of DTF shortening in WA→LR→RC and southern→northern processes through QTL–allele matrix comparisons by using RTM‐GWAS. Core Ideas: In CSGP, 177 DTF QTLs with 797 alleles explaining 95.15% phenotypic variation were identified. 83 QTL & 207 alleles changed in WA→LR→RC and southern→northern; eight new loci emerged in LR and RC. Allele inheritance, emergence, exclusion, and recombination played genetic drivers in WA→LR→RC. In southern→northern, genetic drivers played differently for DTF shortening in WA vs. LR plus RC. Further shortening potential of DTF (4.2–11.1 d) was predicted in CSGP.